Original articleTolerance and efficacy of preoperative intracavitary HDR brachytherapy in IB and IIA cervical cancer - Białas, Brygida; Kellas-Sleczka, Sylwia; Fijałkowski, Marek; Raczek-Zwierzycka, Katarzyna (Journal of Contemporary Brachytherapy, 2009)
Purpose: The aim of this work is to analyze the efficacy and tolerance of preoperative intracavitary HDR brachytherapy (HDR-BT) in patients with IB and IIA cervical cancer. Material and methods: 139 patients with cervical cancer IB-IIA with preoperative HDR-BT, out of which 60 patients with cervical cancer IB (43.2%) and 79 with IIA (56.8%) were treated since 1996 to 2002. In preoperative BT total dose to point A ranged from 30-45 Gy in 6-9 fractions twice a week. The fraction dose was 4-5 Gy at point A. Six weeks after BT all patients underwent radical Wertheim-Meigs hysterectomy. Patients with disadvantageous risk factors or with positive specimen histology had a complementary therapy: external-beam radiotherapy (EBRT) given to the whole pelvic volume in daily fractions of 2 Gy up to total dose of 36-52 Gy (20 patients) or EBRT with cisplatin-based chemotherapy with the dose of 30-40 mg/m 2 in 5-7 fractions given weekly (7 patients) or chemotherapy (6 patients). Acute and late radiation toxicity was evaluated according to EORTC/RTOG. Results: In postoperative specimen histopathology the number of 114 women (82%) had tumor-free specimen within brachytherapy target (in cervix and cavity), 96 women (60.1%) had tumor-free specimen both in and outside brachytherapy target (lymph nodes, parametra, adnexis). The 5-year and 10-year DFS were 93.8% and 88% for IB and 89.7% and 64.7% for IIA respectively. 7.9% of patients developed acute toxicity both in rectum and bladder (only in I and II grade of EORTC/RTOG). Late severe complication occurred in rectum in 2.2% of patients and in bladder 1.4%. Conclusions: 1. Preoperative HDR-BT in patients with IB and IIA cervical cancer is an effective and well tolerated therapy with acceptable rate of side effects. 2. Preoperative HDR-BT followed by surgery in a group without risk factors is a sufficient treatment option with no additional adjuvant therapy requirement.